Effective solution for improving rheological properties of cement paste containing zeolite. (10th October 2022) - Wang, Qing; Xiong, Zihao; He, Jianqiang; Lai, Mianheng; Ho, Johnny
Highlights: Pore size distribution of zeolite powder varies under calcination. Yield stress of paste is effectively decreased by substituting calcined zeolite (greater than500℃) instead of natural zeolite. Incorporating calcined zeolite (greater than500℃) in cement paste significantly lowered the plastic viscosity in comparison with natural zeolite. Lower water retaining capacity of calcined zeolite is responsible for better rheological performance in fresh paste. Abstract: Natural zeolite powder is an ideal supplementary cementitious material which can improve the mechanical properties and durability of cement-based materials. However, the porous internal structure and strong water adsorption ability of natural zeolite will inevitably cause fluidity reduction in cementitious system. In the present study, calcination methods are proposed to investigate the rheological property change in cement paste containing zeolite. By XRD analysis, BET test, particle size distribution determination and SEM observation, the chemical and physical changes of natural and calcined zeolite (100 ℃, 500 ℃ and 700 ℃) were explored comprehensively. Afterwards, rheological tests of cement paste incorporated with zeolite were carried out to understand the mechanism of calcined zeolite on its rheological properties. Results indicate than calcination above 500 °C effectively optimizes the pore structure of zeolite and mitigates the negative impact brought by natural zeolite on the rheological properties. Better water release capacity and weaker frictional interaction of solid particle after calcination are responsible for the improvement on the rheological performance of cement pastes containing zeolite.